Regioselective ring opening of aziridine for synthesizing azaheterocycle - Srivastava, Nikhil; Ha, Hyun-Joon (Frontiers in Chemistry, 2023)
Aziridine had different regioselective ring openings depending on the functional group of its alkyl substituent. In the case of the alkyl group bearing γ-ketone at the C2 substituent of aziridine, the ring opening by the hydroxy nucleophile from H2O occurred by attacking the aziridine carbon at the C2 position. This reaction proceeded efficiently in the presence of CF3CO2H. Interestingly, the same starting aziridine ring bearing the alkyl substituent at the C2 position with the γ-silylated hydroxy group instead of γ-ketone led to the ring-opening reaction by the same oxygen nucleophile at the unsubstituted C3 position, with the breakage of the bond between aziridine N1 nitrogen and carbon at C3. These reaction products were cyclized to afford substituted pyrrolidine and piperidine rings with representative examples of congeners of pseudoconhydrine and monomorine.